Exploring library management support for enhancing self-directed learning: narratives from research-support librarians - A. Samah, Nazrinda; Mohd Tahir, Lokman; Wan Mamat, Wan Ali @ Wan Yusoff (Emerald Publishing, 2021)
Purpose: This qualitative study explores the issue of library management support in providing a self-directed learning environment for research-support librarians which is an under-explored feature of librarianship in Malaysian public university libraries.